Table of Content - - (Journal of Arabic Language Sciences and Literature, 2025)
:Table of Content• A thematic and artistic comparison between the poems "Sunset Garden" and "Fever" by Ghazi Al-GosaibiDr. Khalid Saleh Alshedookhi• Literary Taste Between Al-Qadi Al-Jurjani and Abdul-Qahir Al-Jurjani: A Comparative StudyMr. Mūsā Hādī Al-Fayfī• The sufficiency of contrastive interpretation in the novel: "As If It Were a Canopy" by Moroccan Author Suad Al-Nasser, as a modelDr. Sanae Harboul• The Aesthetics of the Arabic Language in Expressing Human Relationships: A Rhetorical-Analytical Study Between Tradition and Contemporary ContextsMr. Fahad Nawaf Alotaibi• The Point of View in the Saudi Novel Between the Narrator and the Author: Selected ModelsMs. Aliah Radatallah Al-Mozainy• Linguistic Roots of Surah At-Tariq: Structure and Morphological SignificanceDr. Rana Abdel-Aziz Al-Gharawi
Keywords: Journal of Arabic Language and Literature